Structural model of a bacterial focal adhesion complex - Christian Cambillau; Tâm Mignot (Communications Biology)
Abstract Cell movement on surfaces relies on focal adhesion complexes (FAs), which connect cytoskeletal motors to the extracellular matrix to produce traction forces. The soil bacterium Myxococcus xanthus uses a bacterial FA (bFA), for surface movement and predation. The bFA system, known as Agl-Glt, is a complex network of at least 17 proteins spanning the cell envelope. Despite understanding the system dynamics, its molecular structure and protein interactions remain unclear. In this study, we utilize AlphaFold to generate models based on the known interactions and dynamics of gliding motility proteins. This approach provides us with a comprehensive view of the interactions across the entire complex. Our structural insights show the connection of essential functional modules throughout the cell envelope and offer an inspiring view of the force transduction mechanism from the inner molecular motor to the exterior of the cell.